Open relationships - challenges and dilemmas - Krystian Wdowiak; Agnieszka Maciocha; Julia Wąż; Aleksandra Witas; Weronika Chachaj; Paulina Słomka; Ewa Gardocka (Kazimierz Wielki University, 2024)
Introduction and objective: Consensual non-monogamy (CNM) refers to various relationship types in which at least one partner, with the other's consent, forms sexual and/or emotional connections with other people. In open relationships, partners are allowed to engage sexually with others, but emotional intimacy is reserved for the primary relationship, which takes precedence. The aim of this article is to gather the most up-to-date information on open relationships. Material and methods: A review of studies available on the PubMed platform (https://pubmed.ncbi.nlm.nih.gov/) was conducted, including articles with free full-text access that used the keywords: "open relationship", "CNM" and "Consensual non-monogamy." Brief Description of the State of Knowledge: CNM includes open relationships, polyamory, polyfidelity, and swinging. Interest in open relationships has increased in recent years, with more people expressing curiosity about them than those actively participating. Men, individuals with high cognitive empathy, those less prone to jealousy, and those capable of experiencing compersion-the joy from a partner's involvement with others-are particularly interested in open relationships. Summary:  Research suggests potential benefits of CNM, including greater relationship and sexual satisfaction compared to monogamous arrangements. However, open relationships can also pose challenges such as social stigma, the potential breakdown of the primary relationship, or complications in parenting for those involved. Despite growing interest, CNM and phenomena like compersion remain under-researched, providing an open field for further investigation into their dynamics and impact on individual and relational well-being.